Analisis Kurikulum 2013 Terhadap Pembentukan Nalar Kritis Dan Karakter Siswa - Devin Wiranda; Siti Tiara Maulina (Shofanah Media Berkah, 2023)
Education is an important component that cannot be ignored, education leads people to better human resources. Education is a place where the character of students is formed. The more developed the times, it is fitting for students or youth to think critically towards superior human resources. as in Law No. 20 of the year concerning the national education system (article 12 paragraph 1) it is stated that education has formal, non-formal and informal channels. This research will focus on formal education and analyze the 2013 curriculum strategy for the formation of critical thinking and student character.